Studentsâ€™ Passiveness in Speaking English at English Education Department Universitas Muhammadiyah Yogyakarta - Erma Fitriani (PBI 15 UMY 027, 2015)
*27 An active learning is an important thing for students in the learning process. It can bring positive effect for students and lecturers, especially in speaking English in the learning process. However, there were some students who did not participate and some of students remained silent during English language learning process. Therefore, this research explained studentsâ€™ passiveness in Speaking English at English Education Department of Universitas Muhammadiyah Yogyakarta. This research aimed to reveal the level of studentsâ€™ passiveness in Speaking English and to find out the causes of studentsâ€™ passiveness. The researcher would like to reveal whether the studentsâ€™ passiveness in Speaking English at English Education Department batch 2012 very high, high, low or very low. Additionally, the researcher also investigated the causes that made students become passive in Speaking English. This research used quantitative research design. The population of this research was English Education Department batch 2012 and there were 60 respondents of this research. The instrument of this research was questionnaire. The researcher used SPSS version 20 as the tool to process the data. After that, the researcher made descriptive statistic to interpret the data into sentences. There were two results of this research. The first result showed that studentsâ€™ passiveness in Speaking English at English education department were â€œhighâ€. There were 55% students agreeing that they were as passive students in English language learning process. The second result showed that the big causes that made studentsâ€™ passiveness were comfortableness and not conducive XII classroom atmosphere. There were 48.01% students agreed that they had some causes that made them being passive in English language learning process. After the researcher conducted this research, English Education Department needed improvement, especially in teaching and learning process to improve studentsâ€™ activeness in Speaking English. The researcher suggested to the future researcher to conduct a new research that focused on the strategies to improve studentsâ€™ activeness in Speaking English at English Education Department. On the other hand, lecturers at English Education Department Universitas Muhammadiyah are expected to create new strategies to help passive students become active in learning activities. Finally, the institution also had important role toward this problem. The institution was expected to conduct a seminar for lecturers about teaching strategies to overcome passive students in English language learning process.